Taken by storm: Hurricanes, migrant networks, and US immigration - Mahajan, Parag and Yang, Dean (American Economic Journal: Applied Economics)
Do negative shocks in origin countries encourage or inhibit international migration? What roles do networks play in modifying out-migration responses? The answers to these questions are not theoretically obvious, and past empirical findings are equivocal. We examine the impact of hurricanes on a quarter century of international migration to the United States. Hurricanes increase migration to the United States, with the effect's magnitude increasing in the size of prior migrant stocks. We provide new insights into how networks facilitate legal, permanent US immigration in response to origin country shocks, a matter of growing importance as climate change increases natural disaster impacts. - Reproduced